Analysis of Students' Mathematical Problem Solving Ability in Solving HOTS Problems in terms of Mathematical Resilience - Fitria Dwi Nurjannah; Hella Jusra (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
This research purposed to describe students' mathematical problem solving abilities in solving HOTS questions based on mathematical resilience. This type of research is descriptive qualitative research with the subjects of this study were class VII students, totaling 218 students who were selected by purposive sampling. The research subjects were grouped into 3 categories based on mathematical resilience: high, medium, and low. The instrument used is a mathematical resilience questionnaire, a written test of mathematical problem solving ability, and an interview. This study indicates that from 115 students, there are 8 students with low mathematical resilience category, 79 students with medium mathematical resilience category, and 28 students with high mathematical resilience category. Some students are in the category of moderate mathematical resilience. And each high, medium and low category has different mathematical problem solving abilities in solving HOTS questions.